Cost effective recovery of lithium from lithium ion battery by reverse osmosis and precipitation: a perspective. Issue 2 (30th June 2017) - Swain, Basudev
Abstract: Production of lithium from primary resources is lagging behind demand (12% versus 16% in 2016), cost of lithium is increasing (between 40 and 60% in 2016), battery energy density rapidly increasing versus declining cost, and estimated lithium ion battery (LIB) markets size (77.42 billion by 2024) driven by projected demands for plug‐in electric vehicles (PEVs) clearly justifies recycling. PEV technology and projected demand raise several challenges, including lithium demand/scarcity and future technology to recover lithium from LIB waste. To address the circular economy, steady supply chain security, self‐reliance, environment safety, environment directive, energy security, resources conservation, futuristic carbon footprint, WEEE directives and waste crime, recycling of LIB is an absolute essential. During the last decade, LIB recycling research and industrial recycling of LIB have attracted the interest of researchers, industrialists, and environmentalists. All have reported progress in the recovery of valuable metals like Co, but have rarely focused on lithium recovery. Hence, this paper addresses logical hypothesis and application of available technology in a fashion where lithium recycling from LIB can be addressed. © 2017 Society of Chemical Industry